Maulid Nabi Tradition as Cultural Da’wah: Constructing Muslim Identity and Social Power in Southeast Asia - Zakki, Ahmad (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Although the Prophet’s Birthday (Maulid Nabi) is not explicitly prescribed as a religious observance in Islamic scripture, its widespread practice across Southeast Asia demonstrates how religious traditions are continuously shaped by social, cultural, and political contexts. Existing studies have predominantly examined Maulid as a form of religious devotion, cultural heritage, or local religious expression, while comparative analyses of how Maulid functions as a site of power formation and contestation across different Muslim societies remain limited. This study addresses this gap by examining how Maulid traditions operate within distinct configurations of authority, identity, and social practice in Brunei Darussalam, Pattani (Thailand), and Indonesia. Drawing on Foucault’s discourse theory of power and Bourdieu’s theory of practice, the study employs a comparative qualitative approach based on the analysis of relevant literature, historical accounts, and documented Maulid practices. The findings demonstrate that Maulid is not merely a ritual commemorating the Prophet’s birth but a socially embedded practice through which religious authority, political legitimacy, and collective identity are produced and contested. In Brunei Darussalam, state-sponsored Maulid celebrations contribute to the symbolic reinforcement of the Sultan’s sovereign authority. In Pattani, Maulid functions within particular social contexts as a marker of Malay-Muslim identity and, for some groups, as a symbolic expression of resistance to dominant political structures. In Indonesia, the celebration has become an arena of contestation between traditionalist and puritan-oriented interpretations of Islamic practice. By comparing these three contexts, this study advances existing scholarship by demonstrating that Maulid constitutes a dynamic arena in which religious practice intersects with power relations, cultural identity, and political authority. The study therefore contributes a comparative perspective to the sociology of Islamic ritual and da’wah studies by conceptualizing Maulid as a form of cultural da’wah whose social and political meanings are contingent upon the structures within which it is practiced.